Effect of Items Disclosed in the GRI G4-Based Sustainability Reports on Company Value - Anggi Bimantara (Journal of Contemporary Information Technology, Management, and Accounting, 2022)
This research focuses on each item and category disclosed in the latest sustainability report, namely GRI G4. The purpose of this research is to analyze and find out the effect of the disclosure of each item on the economic, social, and company categories on firm value. Given that companies are actually required not to pay attention to economic matters or financial performance, but further than this. The research method used is a quantitative method. The data source used is secondary data. The study population is all companies listed on the IDX. The research sample used non-probability, namely the purposive sampling method with the requirements of the company to publish successive sustainability and financial reports from 2017 to 2019, and is still actively listed on the Indonesia Stock Exchange (IDX). Data collection techniques use an electronic system such as PC,laptop devices,and use several website links as support. The results of this study indicate that the economic, environmental, and social categories disclosed in the sustainability report do not have a significant effect on firm value. Thus it shows that no matter how complete the published disclosures are, the results do not have any influence on firm value.